Kleptoparasitism of wintering Great Northern Divers Gavia immer by gulls - Byrkjedal, Ingvar (Ornis Norvegica, 2011)
Four cases are described of wintering Great Northern Divers Gavia immer being attacked by gulls (Herring Gull Larus argentatus in three of the cases, Greater Black-backed Gull Larus marinus in one) while handling flounder (Pleuronectiformes) on the sea surface. In each case the gull tried to steal the divers' prey without success. The divers saved their prey either by diving with prey in bill, or by dropping prey into the sea and retrieving it after attacking the gull.